2018
DOI: 10.1152/japplphysiol.01078.2017
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory muscle training reduces diaphragm activation and dyspnea during exercise in COPD

Abstract: Among patients with chronic obstructive pulmonary disease (COPD), those with the lowest maximal inspiratory pressures experience greater breathing discomfort (dyspnea) during exercise. In such individuals, inspiratory muscle training (IMT) may be associated with improvement of dyspnea, but the mechanisms for this are poorly understood. Therefore, we aimed to identify physiological mechanisms of improvement in dyspnea and exercise endurance following inspiratory muscle training (IMT) in patients with COPD and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
97
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(113 citation statements)
references
References 53 publications
(82 reference statements)
7
97
0
9
Order By: Relevance
“…In a recent study Langer et al [96] showed that supervised IMT in patients with severe COPD and baseline inspiratory muscle weakness was associated with increased inspiratory muscle strength, reduced dyspnea, and improved exercise tolerance compared with sham training (Fig. 7).…”
Section: Inspiratory Muscle Training (Imt)mentioning
confidence: 95%
“…In a recent study Langer et al [96] showed that supervised IMT in patients with severe COPD and baseline inspiratory muscle weakness was associated with increased inspiratory muscle strength, reduced dyspnea, and improved exercise tolerance compared with sham training (Fig. 7).…”
Section: Inspiratory Muscle Training (Imt)mentioning
confidence: 95%
“…As the inspiratory muscles might become already trained [ 22 ], IMT is not effective in patients with COPD and high MIP (inspiratory muscle function > 60 cmH 2 O) [ 6 ]. Moreover, earlier studies showed that IMT induced respiratory muscle strength and deeper breathing, reduced f R, and contributed to dyspnea relief and the improvement of exercise tolerance in patients with COPD and maintained BMI [ 13 ]. Hence, IMT had been hypothesized to improve dynamic hyperinflation by reinforcing inspiratory muscles [ [8] , [9] , [10] ].…”
Section: Discussionmentioning
confidence: 99%
“…From the observations abovementioned, IMT might change a breathing pattern other than dynamic hyperinflation and subsequently affect exercise tolerance in patients with COPD. Given that IMT activates inspiratory muscles and induces deeper breathing [ 12 , 13 ], we hypothesized that the improvement of exercise tolerance might be depended on the degree of ventilatory efficiency obtained from IMT.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, participation in pulmonary rehabilitation is recommended as a pivotal intervention in symptomatic COPD regardless the severity of resting functional impairment . Beneficial changes in "respiratory responses" such as exertional ventilation (O'Donnell et al, 1998;Porszasz et al, 2005;Puente-Maestu et al, 2006), breathing pattern (O'Donnell et al, 1998), operating lung volumes (Porszasz et al, 2005;Puente-Maestu et al, 2006) and static respiratory muscle strength (Charususin et al, 2018;Langer et al, 2018) have been reported after training. These changes are, however, not particularly large and frequently inconsistent (Neder et al, 2019).…”
Section: Introductionmentioning
confidence: 99%